A tailored flexible vaginal pessary treatment for pelvic organ prolapse in older women. Issue 9 (12th May 2021) - Gold, Ronen S.; Baruch, Yoav; Amir, Hadar; Gordon, David; Groutz, Asnat
Abstract: Objectives: To present a flexible protocol of vaginal pessaries for older women with significant pelvic organ prolapse (POP). Design: A prospective cohort study of 140 consecutive older women (aged ≥65 years) with significant POP treated with individually fitted vaginal pessaries. After initial insertion, each patient was invited for a first evaluation after 1 month and subsequent follow‐ups at increasing intervals of 1 month. During each examination, the pessary was removed and the vagina was inspected for infection, bleeding, or erosions. All patients were advised to use a vaginal estrogen cream twice a week. Setting: The study was conducted during 2020 in the urogynecology clinic of a tertiary medical center. Participants: The study cohort included 140 consecutive older women with significant and symptomatic POP treated with vaginal pessaries. Main outcome: Primary outcomes included time intervals between follow‐up visits, pessary‐associated complications, need to change the pessary, need to remove the pessary temporarily, and whether the patients eventually underwent POP surgery. Results: The mean age of the patients at the time of pessary fitting was 76.7 ± 9.2 years (range 65–100 years). Mean interval between follow‐up examinations was 3.3 ± 1.1 months (range 1–6 months). Most patients (83.6%) used a ring pessary with support, but only a small number of patients were able to maintain the pessary by themselves. Of the 140 patients, five (3.6%) patients only eventually underwent POP surgery, and in 11 (7.9%) patients, the vaginal pessary had to be removed for 2–4 weeks because of significant vaginal discharge or superficial erosions. Additionally, 12 (8.6%) patients developed stress urinary incontinence following pessary insertion. Conclusions: Customized management with vaginal pessary for symptomatic POP in older women is effective and safe, and is a suitable therapeutic alternative for older women who are unable or unwilling to undergo reconstructive pelvic surgery.